Hubungan Pengetahuan dengan Sikap Pemilihan Kosmetika Perawatan Rambut pada Mahasiswa Tata Rias dan Kecantikan Fakultas Pariwisata dan Perhotelan Universitas Negeri Padang - Olivia Shaqilla; Tyas Asih Surya Mentari (Mutiara : Jurnal Penelitian dan Karya Ilmiah, 2025)
This study analyzes the relationship between knowledge and attitudes toward the selection of hair care cosmetics among students of the Cosmetology and Beauty Program at Universitas Negeri Padang. The aim of this research is to determine the extent to which students’ level of knowledge is related to their attitude in choosing appropriate and safe hair care cosmetic products. The study employs a quantitative approach with a correlational design. Data were collected using a questionnaire distributed to 78 students from the 2023 academic cohort. Data analysis was conducted using simple linear regression with the help of SPSS version 20. The results show that both the level of knowledge and the attitude of students are categorized as very good. The regression analysis yielded a significance value of 0.009 (< 0.05), indicating a significant relationship between knowledge and attitude. The regression coefficient of 0.328 suggests that each unit increase in knowledge contributes positively to students’ attitudes in selecting hair care cosmetics. These findings emphasize the importance of cosmetic education in encouraging students to develop a more selective and thoughtful approach when choosing products that are suitable and safe.